The Human Desmin Promoter Drives Robust Gene Expression for Skeletal Muscle Stem Cell-Mediated Gene Therapy - Jonuschies, Jacqueline; Antoniou, Michael; Waddington, Simon; Boldrin, Luisa; Muntoni, Francesco; Thrasher, Adrian; Morgan, Jennifer (Current Gene Therapy, 2014)
Lentiviral vectors (LVs) represent suitable candidates to mediate gene therapy for muscular dystrophies as they infect dividing and non-dividing cells and integrate their genetic material into the host genome, thereby theoretically mediating longterm expression. We evaluated the ability of LVs where a GFP reporter gene was under the control of five different promoters, to transduce and mediate expression in myogenic and non-myogenic cells in vitro and in skeletal muscle fibres and stem (satellite) cells in vivo. We further analysed lentivirally-transduced satellite cell-derived myoblasts following their transplantation into dystrophic, immunodeficient mouse muscles. The spleen focus-forming virus promoter mediated the highest gene expression in all cell types; the CBX3-HNRPA2B1 ubiquitously-acting chromatin opening element (UCOE) promoter was also active in all cells, whereas the human desmin promoter in isolation or fused with UCOE had lower activity in non-muscle cells. Surprisingly, the human skeletal muscle actin promoter was also active in immune cells. The human desmin promoter mediated robust, persistent reporter gene expression in myogenic cells in vitro, and satellite cells and muscle fibres in vivo. The human desmin promoter combined with UCOE did not significantly increase transgene expression. Therefore, our data indicate that the desmin promoter is suitable for the development of therapeutic purposes.
Keywords: Duchenne Muscular Dystrophy